Bio-based activated carbon for Cu(II), Ni(II), and Pb(II) ions aqueous sequestration : physiochemical characterization, isotherms, and kinetics - Muhammad, Imran-Shaukat; Rafeah, Wahi; Zainab, Ngaini (Springer Nature, 2024)
Several biomass waste categories are being used to generate a variety of value-added products due to their natural abundance and low cost. Melia azedarach waste biomass is burned since no industrial application has been identifed. To identify a better utilization, activated carbon was produced from Melia azedarach leaves and twigs through the molten salt synthesis technique with 10% ZnCl2 at 500 °C for 2 h. Activated carbons based on Melia azedarach leaves and twigs had surface areas of 121.592 m2 g−1 and 91.423 m2 g−1, respectively. Both activated carbons were applied in batch adsorption of Cu(II), Pb(II), and Ni(II) ions in aqueous medium. The maximum Cu(II), Pb(II), and Ni(II) removal by the leaves activated carbon was 97.67%, 97.03%, and 69.60%, respectively, adsorption capacity was 48.63 mg g−1, 48.51 mg g−1, 34.80 mg g−1, respectively at 50 ppm initial concentration, 1 g L−1 adsorbent dose, 5 solution pH, 26 °C temperature, and 120 min contact time. At the same process parameters, the twigs activated carbon expressed maximum Cu(II), Ni(II), and Pb(II) ions removal as 89.41%, 51.63%, and 61.64%, respectively, adsorption capacity was 44.71 mg g−1, 30.82 mg g−1, 25.81 mg g−1, respectively. The equilibrium data ftted with Freundlich isotherm for Pb(II), and Ni(II), while Temkin isotherm for Cu(II) adsorption. Pseudo second order kinetic model was followed by both the adsorbents in heavy metal ions adsorption. This work is signifcant because biomass based activated carbons have exhibited excellent adsorption capabilities for heavy metals in aqueous media.